Design of a robotic manipulator for handling products of automotive industry. (18th February 2020) - Blatnický, Miroslav; Dižo, Ján; Gerlici, Juraj; Sága, Milan; Lack, Tomáš; Kuba, Erik
Automation is a process of handling and transport of products, which allows replacing man's control by operation of manipulators and robots. It represents a highly complex process, which includes several operations and they are usually performed automatically by particular devices. In this article, a technical design of a universal versatile robotic manipulator for handling with automotive products is presented. The designed device is intended for handling with automotive products with a maximum weight of 25 kg. The technical solution of the manipulator comes from required specifications and operation conditions given by the customer, who will install it as a part of an automatic line. A particularity of the manipulator is the special functionality, which allows handling with objects of both circular and angular shapes. This is ensured by adaptable gripping fingers, which are able to adjust their position by means of a well-considered mechanism. The technical design of the manipulator includes calculation of forces needed for reliable gripping of manipulated objects, choice of a working screw and calculation of the load and carrying out of strength analyses of the main loaded part of the manipulator. Based on results, there is recommended an appropriate material for the manufacture of the device to reach its optimal accuracy of positioning of handled objects during a long-term operation.